1983
DOI: 10.1177/014662168300700208
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Common Metric in Item Response Theory

Abstract: A common problem arises when independent esti mates of item parameters from two separate data sets must be expressed in the same metric. This problem is frequently confronted in studies of horizontal and ver tical equating and in studies of item bias. This paper discusses a number of methods for finding the appro priate transformation from one metric to another met ric and presents a new method. Data are given com paring this new method with a current method, and recommendations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
154
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(170 citation statements)
references
References 3 publications
0
154
0
1
Order By: Relevance
“…24 In this process, the 5 to 10 conserved questions acted as anchor points. The IRT equate software first compared the calculated IRT question parameters for each year on these particular questions.…”
Section: Irt Equating Methodsmentioning
confidence: 99%
“…24 In this process, the 5 to 10 conserved questions acted as anchor points. The IRT equate software first compared the calculated IRT question parameters for each year on these particular questions.…”
Section: Irt Equating Methodsmentioning
confidence: 99%
“…Lord continued to contribute to IRT methodology with works by himself as well as coauthoring works dealing with unbiased estimators of ability parameters and their parallel forms reliability (1983d), a four-parameter logistic model (Barton and Lord 1981), standard errors of IRT equating (1982), IRT parameter estimation with missing data (1983a), sampling variances and covariances of IRT parameter estimates (Lord and Wingersky 1982), IRT equating (Stocking and Lord 1983), statistical bias in ML estimation of IRT item parameters (1983c), estimating the Rasch model when sample sizes are small (1983b), comparison of equating methods , reducing sampling error , conjunctive and disjunctive item response functions (1984), ML and Bayesian parameter estimation in IRT (1986), and confidence bands for item response curves with Pashley (Lord and Pashley 1988).…”
Section: Further Developments and Evaluation Of Irt Modelsmentioning
confidence: 99%
“…The item parameters for item j on Scale J are , , and ; the item parameters for item j on Scale I are , , and . Kim and Lee (2006) indicated that there are four scale linking methods which are applicable to mixed-format tests: the mean/sigma (Marco, 1977), mean/mean (Loyd & Hoover, 1980), Haebara (1980), and Stocking and Lord (1983). Mean/mean and mean/sigma methods are referred to as moment methods while the Haebara and, Stocking and Lord methods are referred to as characteristic curve methods (Kolen & Brennan, 2004).…”
Section: Irt Test Equatingmentioning
confidence: 99%